Phenotypic plasticity of European larch radial growth and wood density along a-1,000 m elevational gradient - Escobar Sandoval, Margarita; Pâques, Luc; Fonti, Patrick; Martinez Meier, Alejandro; Rozenberg, Philippe (Wiley, 2021)
Phenotypic plasticity is a key mechanism for sedentary long-living species to adjust to changing environment. Here, we use mature Larix decidua tree-ring variables collected along an elevational transect in the French Alps to characterize the range of individual plastic responses to temperature. Stem cores from 821 mature Larix decidua trees have been collected from four plots distributed along a 1,000-m elevational gradient in a natural forest to build up individual linear reaction norms of tree-ring microdensity traits to temperature. The sign, magnitude and spread of variations of the slopes of the individual reaction norms were used to characterize variation of phenotypic plasticity among plots and traits. Results showed a large range of phenotypic plasticity (with positive and negative slopes) at each elevational plot and for each tree-ring variable. Overall, phenotypic plasticity tends to be larger but positive at higher elevation, negative at the warmer lower sites, and more variable in the center of the elevation distribution. Individual inter-ring reaction norm is a valuable tool to retrospectively characterize phenotypic plasticity of mature forest trees. This approach applied to Larix decidua tree-ring micro-density traits along an elevation gradient showed the existence of large inter-individual variations that could support local adaptation to a fast-changing climate.